A comparative study of aqueous and organic processed Li1.2Ni0.2Mn0.6O2 Li-rich cathode materials for advanced lithium-ion batteries. (1st September 2017) - Iturrondobeitia, A.; Kvasha, A.; Lopez del Amo, J-M.; Colin, J.F.; Sotta, D.; Urdampilleta, I.; Casas-Cabanas, M.
Abstract: The influence of the solvent used in the processing of Li1.2 Ni0.2 Mn0.6 O2 Li-rich electrodes has been thoroughly studied using complementary chemical, structural and electrochemical characterization techniques. Structural characterization has demonstrated that the bulk chemical composition and the structure of the material remain unchanged when processing the electrode in organic and aqueous media. 6 Li solid state NMR measurements revealed that no perceptible variations of the signal positions and intensities were observed for the different samples, indicating the absence of H + /Li + ionic exchange upon water exposition. Full coin-cells with the waterborne and organic processed Li-rich cathodes and graphite anodes delivered exceptional capacity retention during more than 250 cycles at 100% depth of discharge. This study proves that water-based binders can be used both for the anode and the cathode formulations of the next generation of Li-ion batteries.